2003
DOI: 10.1002/app.12041
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous nucleation of nylon 6 and PET with selected inorganic compounds

Abstract: ABSTRACT:The effect of several inorganic compounds in the heterogeneous nucleation of poly(ethylene terephthalate) (PET) and poly(caprolactam) (nylon 6) was studied. Six inorganic chemicals were specifically selected, on the basis of their crystal structure, basal lattice dimensions, and thermal properties, in order to study the effect of temperature in their nucleation capabilities. Considering that temperature is one of the most important variables involved during processing of thermoplastics, the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…As more silver species arrive, the originally separated silver seeds will grow and eventually connect to neighbouring ones. As a result of this kind of growth, a continuous layer of Ag polycrystals forms on the fibre surface; (2) Such bombardments probably scatter ion [13] and/or break the original chemical or absorbed bonds of the atoms/molecules on the substrate surface, which can change molecular degrees [18] and interface-phase structures between silver and the surface of the organic material [19], causing the ions to diffuse and/or depart out from the fibres. The effect not only baffles and retards further-arrived silver species to be adhered or adsorbed, but also has opportunity to break silver-silver crystal bonds to form boundaries, or to cleave nanocrystal grains into smaller ones, or break the silver-fibre bonds to desquamate silver coating.…”
Section: Resultsmentioning
confidence: 99%
“…As more silver species arrive, the originally separated silver seeds will grow and eventually connect to neighbouring ones. As a result of this kind of growth, a continuous layer of Ag polycrystals forms on the fibre surface; (2) Such bombardments probably scatter ion [13] and/or break the original chemical or absorbed bonds of the atoms/molecules on the substrate surface, which can change molecular degrees [18] and interface-phase structures between silver and the surface of the organic material [19], causing the ions to diffuse and/or depart out from the fibres. The effect not only baffles and retards further-arrived silver species to be adhered or adsorbed, but also has opportunity to break silver-silver crystal bonds to form boundaries, or to cleave nanocrystal grains into smaller ones, or break the silver-fibre bonds to desquamate silver coating.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular weight distribution was determined by a size exclusion chromatography, with M n = 145,000 and M w = 235,000. The glass transition temperature (T g ) and the melting point temperature (T m ) of PLA 2002D are 58 and 153 • C, respectively [8].…”
Section: Methodsmentioning
confidence: 99%
“…Besides study on addition of an inorganic nucleating agent to enhance crystallization rate of PLLA, it also reported that crystallization rate of PLLA increased with addition of poly(d-lactic acid), PDLA. Intensive studies mainly on the crystallization kinetics have been performed by means of calorimetry [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Its unique molecular structure endues PET with a high glass‐transition temperature and a slow crystallization rate. To achieve appropriate degree of crystallinity, a large number of heterogeneous nucleating additives such as sodium benzoate, talc, and titanium dioxide have been attempted 17–20…”
Section: Introductionmentioning
confidence: 99%
“…To achieve appropriate degree of crystallinity, a large number of heterogeneous nucleating additives such as sodium benzoate, talc, and titanium dioxide have been attempted. [17][18][19][20] In the previous work, 21 we have prepared PET/ MWNTs composites with low percolation thresholds of electrical conductivity and rheology by coagulation method. We find that interfacial interactions exist between PET and MWNTs, which could be a basis for soft epitaxy of PET crystallization.…”
Section: Introductionmentioning
confidence: 99%